Studies of the growth and mineral nutrition of cassava (Manihot esculenta Crantz) grown as an industrial crop - Madakadze, I.C. (Ignacio Casper) (University of Pretoria, 2024)
Dissertation (MSc Agric (Agronomy))--University of Pretoria, 2019.